Effects of COVID-19 pandemy on African health, political and economic strategy - (:unkn) unknown (My University, 2020)
The appearance of COVID-19 is proving to be a difficult challenge not only for Africa but for the whole world. In order to prevent and curb, the leaders of the countries had to introduce health, economic and political changes and regulations, which were repeatedly sharply criticized. Although statistics show that the spread of the virus in Africa was far from the same as in China, Europe or the Americas, the world's strictest restrictions had to be put in place to stop the pandemic. At the same time, Africa has cut itself off from its main supporters, making its economic situation more difficult and risking the already weak stability of African societies.
Keywords: African Research